Fiqih Perbandingan Memanfaatkan Barang Gadai oleh Murtahin dan Penerapannya dalam Gadai Syariah di Indonesia - .sobarna, nanang (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2025)
In sharia pawning practices, problems often arise regarding whether the murtahin is allowed to use the pawned goods for his own benefit or not. Each school of thought has a different rationale and basis for arguments regarding this matter. This research aims to analyze comparative laws regarding the ability of murtahin (pawn recipients) to utilize pawned goods (rahn) based on the perspective of four madhhab imams (Hanafi, Maliki, Syafi'i, and Hanbali) and evaluate its application in sharia pawn products in Indonesia. This research uses a qualitative approach with a comprehensive literature study method, including analysis of classical fiqh books, accredited national journals and indexed international journals. The research results show that there are significant differences in views between the four madzhab imams. The Hanafi Madzhab allows murtahin to use pawned goods on condition that they have explicit permission from the rahin (pawnshop), because it is considered a form of ijarah (lease) agreement. On the other hand, the Maliki school of thought only allows it in emergency conditions or when there is a clear agreement, while still emphasizing the principle of avoiding the element of usury. The Syafi'i Madzhab strictly prohibits the use of pawned goods by murtahin, because it is seen as potential exploitation of the pledgor. Meanwhile, the Hanbali madzhab provides concessions provided that both parties agree and there are real benefits. In the practice of sharia pawning in Indonesia, referring to the Fatwa of the National Sharia Council-Indonesian Ulema Council (DSN-MUI) No. 25/DSN-MUI/III/2002 concerning Rahn, which emphasizes the prohibition on the use of pawned goods by murtahin, except in the context of a separate ijarah contract.